Consensus core outcome rating for the Japanese neonatal pain guidelines - Takeshi Arimitsu; Mio Ozawa; Kaori Gaughwin (Frontiers Media S.A., 2023)
IntroductionThe Japanese Neonatal Pain Guidelines Committee, led by the Japan Academy of Neonatal Nursing, uses the Grading of Recommendations, Assessment, Development, and Evaluation Working Group method to evaluate the quality of evidence and the strength of treatment recommendations. Ratings on the importance of outcomes related to neonatal pain have not been reported. This study aimed to reach a consensus on the importance of outcomes through a guideline panel composed of doctors, nurses, a nurse practitioner, a physical therapist, and families to ensure consistency in systematic reviews of neonatal pain and future revisions to the guidelines.MethodsA total of 26 professionals, including 21 medical personnel from clinical settings and academia and 5 parents from five family associations, participated in 3-stage eDelphi rounds.ResultsThe literature review and discussion identified 75 outcomes that were included in round one. The participants proposed three additional outcomes: 78 outcomes were scored in rounds two and three. Round three scores showed different stakeholder groups in terms of priority outcomes. Seventeen outcomes were included in the final core outcome and were considered critical for decision-making.ConclusionCore outcomes of the development of neonatal pain guidelines in Japan were identified. The assessment process of importance from this study highlights the difference in the perspectives of medical providers and parents on neonatal pain, thus, involving parents in the assessment and as the spokesperson for the infant admitted to the neonatal intensive care unit is important for a more inclusive evaluation of pain prevention and management.